The Secret Garden of Skin Health: A Mini Review of Centella asiatica and Salvia Rosmarinus - Mohammad Asyraf Adhwa Masimen; Muhammad Faiz Zulkifli; Wan Iryani Wan Ismail; Mohd Tarmiezi Abu Jahar; Nurulhusna binti Md Jan; Muhammad Noor Yassin Mohd Yusof; Noorhasmiera Abu Jahar; PM Ridzuan (Asian Journal of Medicine & Health Sciences, 2024)
Amidst increasing demands for skin care solutions, extensive research has been devoted to exploring the properties of natural ingredients, particularly Centella asiatica and Salvia rosmarinus. Centella asiatica is known for its high content of triterpenoids and flavonoids, which provide multiple benefits for the skin, including soothing sensitive skin, reducing inflammation, and improving skin hydration. On the other hand, Salvia rosmarinus contains antioxidant metabolites and has emerged as a potent antioxidant, antiinflammatory, and antimicrobial agent, helping to protect skin from redness and premature ageing. This review employed a systematic approach, involving meticulous research articles and a selection of narrative reviews based on specific inclusion criteria. Databases such as Web of Science, Scopus, Google Scholar, and Research Gate were utilized for this mini-review. A bibliometric analysis was also employed using Bibliometrix software, providing insight into literature trends. Phytochemical analyses shed light on the active compounds in Centella asiatica and Salvia rosmarinus, offering a comprehensive understanding of their roles in promoting skin health, such as collagen synthesis and skin rejuvenation. Furthermore, pharmacological studies supported the efficacy of these compounds in wound healing, inflammation reduction, and UV damage prevention. The bibliometric analysis underscored a global interest in this field, highlighting top institutions, journals, and highly cited articles. Emerging trends, such as “autophagy” and “composites” in Centella asiatica and “enhancement” and “product” in Salvia rosmarinus, indicate evolving research directions. This mini-review consolidates existing knowledge, emphasising the potential of these natural ingredients to meet the ever-evolving demands within the skincare industry.